2010
DOI: 10.1016/j.expneurol.2010.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Experimental colitis triggers the release of substance P and calcitonin gene-related peptide in the urinary bladder via TRPV1 signaling pathways

Abstract: Clinical data provides evidence of high level of co-morbidity among genitourinary and gastrointestinal disorders characterized by chronic pelvic pain. The objective of this study was to test the hypothesis that colonic inflammation can impact the function of the urinary bladder via activation of TRPV1 signaling pathways followed by alterations in gene and protein expression of Substance P (SP) and calcitonin gene-related peptide (CGRP) in sensory neurons and in the bladder. Inflammation was induced by intracol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
86
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 71 publications
4
86
0
Order By: Relevance
“…3). We previously tested if TNBS could also trigger minor bladder inflammation by using MPO assay and H&E staining (34). Analysis of the H&E-stained cross sections of the urinary bladder performed in this study showed that neither RTX nor TNBS (alone or in combination) caused detectable structural changes in the urinary bladder, confirming that the urinary bladder did not develop any signs of acute inflammatory reaction (Fig.…”
Section: Effects Of Efs On the Contractility Of The Detrusor Muscle Asupporting
confidence: 51%
See 4 more Smart Citations
“…3). We previously tested if TNBS could also trigger minor bladder inflammation by using MPO assay and H&E staining (34). Analysis of the H&E-stained cross sections of the urinary bladder performed in this study showed that neither RTX nor TNBS (alone or in combination) caused detectable structural changes in the urinary bladder, confirming that the urinary bladder did not develop any signs of acute inflammatory reaction (Fig.…”
Section: Effects Of Efs On the Contractility Of The Detrusor Muscle Asupporting
confidence: 51%
“…Our previous studies showed that animals with the DAI score of four and above developed distinct histological changes in the colon (thickening of the colonic wall, signs of hemorrhage, etc.) without noticeable histological or biochemical changes in the urinary bladder in this model of colon-bladder crosssensitization (28,34). Because RTX treatment does not lead to the development of hemorrhage, wall thickening, and/or gastrointestinal bleeding, two groups treated either with RTX alone or with RTX-TNBS were not assessed using DAI.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations